Modifications of the Method for Calculating Absolute Drug Bioavailability - Wei Jiang; Juan-juan Yang; Lei Cao; Xue Xiao; Xiao-lian Shi; Yong-xiao Cao (Frontiers Media S.A., 2016)
Purpose: Absolute bioavailability (F) is calculated as the ratio of the area under the plasma drug concentration-time curve (AUC) between extravascular administration and intravenous injection. However, as distribution of a drug after intravenous administration does not reach an equilibrium in the body during the distribution phase, the plasma drug concentration at this phase does not reflect the total amount of drug in the body. The goal of this paper was to analyze the insufficiencies of the method for calculating on absolute bioavailability and to propose a modification to improve the calculation. Methods: Literature reporting absolute bioavailability published during 1983-2014 was searched for ten drug candidates. Plasma drug concentrations representing the amount of drug in the body were then calculated at each time point during the distribution phase according to the plasma drug concentration-time relationship during the elimination phase. Results: The AUC values based on the distribution equilibrium drug concentrations following intravenous injection were 75%±11% of the actually measured drug concentrations in the literature. The absolute bioavailability values in the literature were 76%±12% of the actual bioavailability based on the AUCs from distribution-equilibrium drug concentrations. Conclusions: The present method underestimates the absolute drug bioavailability and should be modified to represent the data more accurately.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.